(3Mbhb GdEfSGf hMQjGJg hOhQ TQYjI GdELQGAGJ GdTQWjI aj JYRjRgG (B:s (3OQGSI JMdjdjI dJMbjb GdJhGRf Hjf Mbhb GdEfSGf hMQjGJg hCef GdeLJeY (B: ((3JTQjYjG habgG hbVGA(B) = Human rights and liberties : the role of the legitimate polic procedures to enhance them : an analytical study to achieve balance between human rights liberties and the security of the society according to (legislations , jurisprudence and judiciary) /s - (3GdOHGS, Ydj eMeO UGdMs; (3CHh RjO, Ydj YdjGf eMeOs ((3YeGf, GdCQOf (B:s (3OGQ GdKbGaI ddfTQ hGdJhRjY,s, 2017)
(3jWQM (B"(3cJGH Mbhb GdEfSGf hMQjGJg(B" (3eaghe Mbhb GdEfSGf hWHjYJgG GdbGfhfjI hPdc ef NdGd HjGf eaghe Mbhb GdEfSGf heGgjJgG h GdJSdSd GdJGQjNj dMbhb GdEfSGf ef GdYUhQ GdbOjeI Edi GdTQjYI GdESdGejI hGdYUQ GdMOjK, haj GdaUd GdKGfj jYQL GdcJGH Ydi Mbhb GdEfSGf aj GdJTQjY GdCQOfj MjK QcR Ydi GdMbhb GdaQOjI hGdeOfjI h GdSjGSjI hGdacQjI h MOO GdcJGH aj GdaUd GdKGdK GdVhGHW GdbGfhfjI hGdELQGFjI dOhQ GdCef aj GdeMGaXI Ydi Mbhb GdEfSGf hGdCMcGe GdYGeI dGSJYeGd GdbhI hGdSdGM hMbhb GdfRdGA aj eQGcR GdEUdGM h GdJCgjd hjJfGhd aj GdaUd GdQGHY GdBKGQ GdbGfhfjI GdeJQJHI Ydi GdeSGS HMbhb GdEfSGf ef bHd CaQGO GdCef GdYGe hHWdGf GdELQGAGJ GdJMbjbjI GdeNGdaI ddTQYjI GdELQGFjI hGdehVhYjI(B.s
(3HHdjhLQGajI (B: (3UaMI (B307-312.s
Keywords: (3Mbhb GdEfSGfs -- (3bhGfjf hJTQjYGJs -- (3GdCQOfs; (3GdTQWIs -- (3bhGfjf hJTQjYGJs -- (3GdCQOfs; (3GdMQjIs -- (3bhGfjf hJTQjYGJs -- (3GdCQOfs